PENGARUH KUALITAS LAYANAN JASA PENDIDIKAN TERHADAP KEPUASAN MAHASISWA DI STMIK MARDIRA INDONESIA BANDUNG - Juhana, Dudung; Mulyawan, Ali (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The study was conducted in STMIK Mardira Indonesia. The results of preliminary studies indicate that student satisfaction in STMIK Mardira Indonesia not optimal. Not optimal for student satisfactions were allegedly caused by factors of service quality include: Physical Evidence, Empathy, Reliability, Responsiveness and Assurance given. According to phenomenon, the problem is formulated in this study as follows: What factors of service quality and student satisfaction STMIK Mardira Indonesia. How the Influence factors of service quality on student satisfaction STMIK Mardira Indonesian either partially or simultaneously. Research method used is descriptive analysis, with a total population of 462 people, and is based on probability sampling with stratified random sampling technique by 5% of precision, then taken into a sample of 215 people. The data analysis technique done by the analysis of the path (Path Analisys) to determine the degree of the relationship between research variables, as well as to determine the effect, either directly or indirectly on the variables. In its operation using SPSS 17 and Ms. Excel. The results showed that the influence of the quality of service simultaneously at 59.4% and residual of 40.06 have been affected by other factors that are not revealed in this study. The direct effect of Physical Evidence 1.66%, Empathy 0.37%, 2.34% Reliability, Responsiveness 10.18% and Assurance 5.24%. while the total effect of Physical Evidence 7.5%, Empathy 3.5%, 10.2% Reliability, Responsiveness 22.7% and Assurance 15.5% Keywords: service quality; student satisfaction